Habit-modifying additives and their morphological consequences on photoluminescence and glucose sensing properties of ZnO nanostructures, grown via aqueous chemical synthesis. (June 2015) - Elhag, Sami; Ibupoto, Zafar Hussain; Khranovskyy, Volodymyr; Willander, Magnus; Nur, Omer
Abstract: Generally, the anisotropic shape of inorganic nano-crystal can be influenced by one or more of different parameters i.e. kinetic energy barrier, temperature, time, and the nature of the capping molecules. Here, different surfactants acting as capping molecules were used to assist the aqueous chemical growth of zinc oxide (ZnO) nanostructures on Au coated glass substrates. The morphology, crystal quality and the photoluminescence (PL) properties of the ZnO nanostructures were investigated. The PL properties of the prepared ZnO nanostructures at room temperature showed a dominant UV luminescence peak, while the "green–yellow" emissions were essentially suppressed. Moreover, the ZnO nanostructures were investigated for the development of a glucose biosensor. An adsorbed molecule has direct contribution on the glucose oxidase/ZnO/Au sensing properties. We show that the performance of a ZnO-based biosensor can be improved by tailoring the properties of the ZnO–biomolecule interface through engineering of the morphology, effective surface area, and adsorption capability. Highlights: Different surfactants were used as the capping molecules. ZnO nanostructures have been grown by the low temperature aqueous chemical. No surfactants dependence was observed to modify the crystallographic structure. The surfactant was affecting the morphology and the PL characteristics. Consequently, the sensing properties can be tailored.